(3GdbdH hGdEHOGds - (3jYbhH Hf ESMGb, CHh jhSa, GHf GdScjJ,J (B224 (3g` s
(3ChdgG (B:s
(3CNHQfG CHh YHO Gddg eMeO Hf GdMSjf GdJfhNi bGd bQCJg Ydi jYbhH Hf GdSejJ hjbGd EfeG GdOfjG dYGYI , Ci eJGY bdjd s
(3BNQgG (B:s
(3ef HGH GdPGd hGdOGd (B: (3CHh YeQh (B: (3jbGd (B: (3eGPG YOhakG hdGYPhakG , Ci de jPb TjFkC adeG NQL bGd jRjO (B: (3Ef abjgce gPG GdOMOGM bUjQ YXje GdHWf s
(3HgG WeSs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B243 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B536s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B183 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs